The ellipticity dependence of Rydberg state excitation of noble gas atoms subject to strong laser fields - Wang, Zhiqiang; Quan, Wei; Hao, Xiaolei; Chen, Jing; Liu, Xiaojun (Frontiers in Physics, 2023)
In this work, we theoretically investigate the ellipticity dependence of the Rydberg state excitation (RSE) and ionization of noble gas atoms subject to strong laser fields at a series of intensities and wavelengthes by a semiclassical model, where the nonadiabtic effect is considered or ignored. Our results demonstrate that, if the nonadiabatic effect has been ignored, the ratio between RSE and ionization yields exhibits an anomalous maximum at a nonzero ellipticity. On the other hand, if the nonadiabatic effect has been considered, this anomalous behavior disappears. The analysis indicates that the absence of this anomalous behavior can be attributed to the nonadiabatic corrections of instantaneous ionization rate and the initial photoelectron momentum distribution at the tunnel exit.